Pengaruh Kompensasi dan Kompetensi Terhadap Kinerja Pegawai Pada Kelurahan Pai Kota Makassar - Bustan Bustan; Rina Rina; hafipah hafipah (Jurnal Online Manajemen ELPEI, 2022)
This research was conducted at the PAI Kelurahan office in Makassar City in mid-December to mid-January. Sampling in this study used as many as 42 respondents. the data collection technique is to use a questionnaire distributed to respondents. the research variables are Compensation (X1), Competence (X2), and Employee performance (Y). This study uses validity and quantitative analysis, to test the level of reliability using Cronbach Alpha and then the data is processed using Multiple Linear Regression Analysis. Hypothesis testing uses the t test with a significance level of 5%. This study uses the SPSS Version 25 tool. From the results of multiple linear regression analysis, it shows that employee performance is influenced by compensation and competency variables. The result of the determination (R2) of one dependent variable. That is 0.970, which means that the performance variable is able to explain 97% of employee performance while the remaining 3% is influenced by other variable factors that were not examined. from the results of the calculation of the t test it can be seen that the compensation and competency variables partially affect employee performance.